What has sight got to do with it? On the representation of concepts in blind children’s drawings - Jaworska-Biskup, Katarzyna (Glottodidactica, 2012)
The paper analyses sample drawings produced by blind children. The focus will be put on the representation of concepts. Major findings gathered in the discussion section show that sight plays complementary rather than primary role in the process of conceptual development, which supports other research in the field of blindness studies conducted so far.